Data journalism practice in Indonesia - Sofia Aunul; Akhmad Fauzy; Siti Aisyah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Data journalism in Indonesia has been evolving rapidly, with practices and challenges that are unique to the region. This article aims to provide an overview of the current state of data journalism in Indonesia, its potential for growth, and the barriers that need to be overcome. This article uses literature review method focusing on 11 publications relating to data journalism practice in Indonesia ranging from year 2018 to 2024. It shows that (1) the availability of open access data from Indonesian government that has some data credibility issues such as less integrated data, lack of raw data and digital divide of internet availability and coverage in some Indonesian region; (2) journalists’ competence of data skills from gathering to displaying (3) decision of building data journalism team is from top authority (4) good narrative enhances news values and audience engagement, (5) data journalism interconnect with news ecosystem in terms of news production and dissemination collaboration. This study underscores the importance of enhancing the competency of Indonesian journalists, particularly in the realm of data journalism. To address this need, developing targeted training programs that improve data literacy and bolster newsroom data journalism teams is crucial. Additionally, future research should explore the impact of data journalism on audience engagement within the Indonesian news media ecosystem, providing insights into how different media platforms can better connect with their audiences. Furthermore, examining the ethical implications of data journalism, including transparency and validity in news production and dissemination, is essential to ensuring that innovation in this field aligns with journalistic integrity.